Student Learning Outcomes in Digestive Systems Material via Deep Learning-Based Problem-Based Learning in High School - Isni Khotimah Br Pane; Aryeni Aryeni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The low effectiveness of conventional learning models in improving students' in-depth understanding and learning outcomes in the digestive system often results in suboptimal learning outcomes. This study aims to determine the effect of the Problem-Based Learning (PBL) model with a deep learning approach on student learning outcomes in the digestive system. The method used was a quasi-experimental with a pretest-posttest control group design. The study population included six classes with samples consisting of two classes: Class XI C as the experimental class (PBL model with a deep learning approach) and Class XI D as the control class (direct instruction method) at High School 1 Batang Kuis. The research instruments included essay tests and student response questionnaires. Results: The findings showed an increase in the average score in the experimental class from 47.1 to 87.5 (an increase of 85.7%), higher than the control class which increased from 46.7 to 81.2 (an increase of 73.8%). The learning completion rate in the experimental class reached 34 students, surpassing the control class which consisted of 27 students. Student responses to the deep learning approach were categorized as very positive, supported by indicators of mindful learning (82%), meaningful learning (72%), and joyful learning (89%). The hypothesis test showed a significant value of 3.649 x 10-5 (<0.05), confirming a significant effect. Practically, this study proves that the integration of PBL and the deep learning approach is an effective strategy for improving learning outcomes and creating meaningful learning experiences for students in complex biology material.